Evaluation of palonosetron and dexamethasone with or without aprepitant to prevent carboplatin-induced nausea and vomiting in patients with advanced non-small-cell lung cancer. Issue 3 (December 2015) - Kusagaya, Hideki; Inui, Naoki; Karayama, Masato; Fujisawa, Tomoyuki; Enomoto, Noriyuki; Kuroishi, Shigeki; Nakamura, Yutaro; Matsuda, Hiroyuki; Yokomura, Koshi; Koshimizu, Naoki; Toyoshima, Mikio; Imokawa, Shiro; et al.
Highlights: Carboplatin-based chemotherapy show relatively strong emetic properties. We assess the efficacy of add-on aprepitant to palonosetron and dexamethasone. Add-on aprepitant provided no improvement in carboplatin-induced emesis. Abstract: Objectives: Although antiemetic management has improved, better control of chemotherapy-induced nausea and vomiting (CINV), particularly during the delayed phase, is needed. The benefit of combination therapy using dexamethasone and the second-generation 5-hydroxytryptamine-3 receptor antagonist palonosetron compared with that of other such receptor antagonists in carboplatin-based chemotherapy is unclear. The effectiveness of adding aprepitant for CINV treatment in moderate emetogenic chemotherapy is also unknown. We compared the efficacy and safety of triple antiemetic therapy using aprepitant, palonosetron, and dexamethasone with that of double antiemetic therapy using palonosetron and dexamethasone in patients with advanced non-small-cell lung cancer receiving carboplatin-containing chemotherapy. Methods: Chemotherapy-naïve patients with non-small-cell lung cancer were enrolled in this prospective controlled study. Eighty patients were randomly assigned to groups receiving either double antiemetic therapy with palonosetron and dexamethasone, or triple antiemetic therapy with aprepitant, palonosetron, and dexamethasone. Complete response rate (no vomiting episode and no rescue therapy) was evaluated as the primary endpoint during the 5-day post-chemotherapy period. Results: The aprepitant add-on and double therapy groups showed overall complete response rates of 80.5% (95% confidence interval [CI]: 68.4–92.6%) and 76.9% (95% CI: 63.7–90.1%; odds ratio [OR]: 0.81; 95% CI; 0.27–2.36; p = 0.788), respectively. Complete responses in the acute and delayed phases and overall incidences of treatment-related adverse events were similar between groups. Conclusion: According to the selection design, triple antiemetic therapy with aprepitant, palonosetron, and dexamethasone was not considered as an option for further studies.